Incorporation of a Multidisciplinary Tumor Board (MTB) in Cancer Patient Care: Experiences of a Comprehensive Cancer Care Hospital in Eastern India - Saha, Mandira; Mohanti, Bidhu Kalyan; Sahoo, Saroj Ranjan; Parida, Sabyasachi; Pattnaik, Jogamaya (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: A multidisciplinary tumor board (MTB) is a critical component of comprehensive cancer care, providing evidence-based treatment recommendations for patients. This analysis aimed to assess the importance of MTB in comprehensive cancer care and evaluate its impact on cancer patient management and treatment compliance. Materials and method: A one-year audit was conducted on patients discussed at the tumor board of a private comprehensive cancer care hospital in Eastern India between September 2020 and August 2021. Data was collected before, during, and after each MTB meeting. Results: A total of 800 cases were discussed during the audit period. Approximately 60% of cases were presented by surgical oncology, 21% by medical oncology, and the remaining by other departments. The median age of patients was 56 years. The most common tumor type was head and neck cancer (28.5%), followed by gastrointestinal and breast cancers (55.2%). The most common treatment plans included surgical management (57.6%), systemic therapy (45%), radiotherapy (32.1%), and palliative care (14.5%). Treatment compliance exceeded 50%, and after one year, 52.87% of patients were still alive. The audit revealed that more than 20% of the data was missing. Conclusion: The MTB practice demonstrated improvements in the management of advanced-stage disease and increased treatment compliance. The audit also highlighted the cancer demographics of this region of India. A prospective trial with a larger patient population, comprehensive follow-up data, and reduced missing data points is recommended for future studies to evaluate the true impact of multidisciplinary care.